GENERAL TRENDS OF PROFESSIONAL TRAINING OF TEACHERS IN THE CONTEXT OF IMPLEMENTATION OF INTERDISCIPLINARY RELATIONS (FOREIGN EXPERIENCE) - Zaskaleta, Svitlana; Shcherbakova, Olena (Educological discourse, 2020)
The article deals with the question of applying the principles of cross-curricular approach in higher education in the countries of the West. The concept of interdisciplinary research is based on the premise that concepts and facts are not studied in isolation from each other. An analysis of the development of higher education in Europe and the US made it possible to highlight its general trend. It defines the application of cross-domain communication principles. Implementation of the cross-curricular approach is considered as a promising method for professional training of students for the application of knowledge in other disciplines. Common terms of this direction are defined. They are: cross-curricular approach, interdisciplinary approach, multidisciplinary approach, cross-disciplinary approach, transdisciplinary approach. A comparative characteristic of integration approaches is proposed. Cross-disciplinary analysis - studies a problem that is usually transformed into one discipline through the prism of another discipline (for example, learning a foreign language of professional communication is studied through profiling disciplines). Multidisciplinary analysis - considers the problem from different points of view, without making a joint effort for the systematic integration of disciplinary views. Inter-disciplinary analysis - considers the problem from different points of view, which leads to a systematic effort to integrate alternative views into a single or holistic framework of analysis The interrelationships between three different approaches are established. Given the differences, the three approaches have much in common. Thus, the level of discipline Multidisciplinary study based on themes. Interdisciplinary skills and concepts are embedded in the standards of the discipline. The transdisciplinary approach takes into account the real life context. In the context of the cross-curricular approach, the integration of scientific literacy with the use of information literacy skills is considered. The purpose of information literacy is to improve both scientific and information literacy of students, the introduction of the concepts of scientific literacy in courses related to relevant topics. This model allows students to better understand scientific information and expand the scientific topics on which the research is conducted. Special attention in the European educational space given to study foreign languages. In the context of an interdisciplinary approach, this means that semantic subjects are taught and studied in a language that is not the student’s native language.